2011
DOI: 10.1016/s1001-0742(10)60466-4
|View full text |Cite
|
Sign up to set email alerts
|

Removal of airborne microorganisms emitted from a wastewater treatment oxidation ditch by adsorption on activated carbon

Abstract: Bioaerosol emissions from wastewater and wastewater treatment processes are a significant subgroup of atmospheric aerosols. Most previous work has focused on the evaluation of their biological risks. In this study, however, the adsorption method was applied to reduce airborne microorganisms generated from a pilot scale wastewater treatment facility with oxidation ditch. Results showed adsorption on granule activated carbon (GAC) was an efficient method for the purification of airborne microorganisms. The GAC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Once the required volume of air had been drawn, the plates were removed from the sampler, covered, inverted, and incubated. The bacteria were incubated on 20 ml nutrient agar medium (LB, Aoboxing Biotech, Co., China) at 37°C for 48 h, and fungi were cultivated on 20 ml Rose Bengal medium (BR, Aoboxing Biotech, Co., China) at 25°C for 72 h (Li et al 2011a). The colonies were counted as colony-forming units (CFU m −3 ) using positive hole correction (Andersen 1958).…”
Section: Microbiological Analysis and Measurementmentioning
confidence: 99%
“…Once the required volume of air had been drawn, the plates were removed from the sampler, covered, inverted, and incubated. The bacteria were incubated on 20 ml nutrient agar medium (LB, Aoboxing Biotech, Co., China) at 37°C for 48 h, and fungi were cultivated on 20 ml Rose Bengal medium (BR, Aoboxing Biotech, Co., China) at 25°C for 72 h (Li et al 2011a). The colonies were counted as colony-forming units (CFU m −3 ) using positive hole correction (Andersen 1958).…”
Section: Microbiological Analysis and Measurementmentioning
confidence: 99%
“…reported that PU was a hydrophobic material [46]. Thus, a hydrophobic interaction between PU and bacteria could also contribute to the bacterial adsorption capacity of PU [47]. Several previous studies have reported that materials containing metal, TiO 2 , and SiO 2 on the surface could have numerous positive charges on their surface [44,46].…”
Section: E Coli Removal Under Dark Conditionsmentioning
confidence: 99%
“…Kara et al reported that removal of a microorganism is a complex process affected by many parameters such as the chemical and physical properties of the adsorbent, the microorganism's characteristics and the environmental conditions [40]. The porous structure and large surface area of the PU are favorable for the adsorption of airborne microorganisms [41]. Yeast can be adhered on the inner surface of the pores of PU by van der Waals force [42].…”
Section: Yeast Removal By Pumentioning
confidence: 99%
“…The yeast adsorption mechanism by PU is also due to its hydrophobicity and non-polarity. Most previous studies reported that microorganisms tend to attach to hydrophobic and non-polar materials [41,43]. Li et al reported that hydrophobic interaction between the yeast cell surface and the adsorbent surface can enable the cell to overcome the repulsive forces within a certain distance from the adsorbent and yeast [41].…”
Section: Yeast Removal By Pumentioning
confidence: 99%